An inductively coupled plasma metal organic chemical vapor deposition based on showerhead structure for low temperature growth. (9th September 2021) - Zhang, Zixuan; Luo, Yi; Yu, Jiadong; Li, Xiang; Wang, Jian; Yu, Wangyang; Wang, Lai; Hao, Zhibiao; Sun, Changzheng; Han, Yanjun; Xiong, Bing; Li, Hongtao
Abstract: An inductively coupled plasma metal organic chemical vapor deposition (ICP-MOCVD) based on showerhead structure is proposed for the low temperature growth of thin solid films including GaN. The flow field of precursors in the chamber of ICP-MOCVD was analyzed and the structure of showerhead was optimized by changing the showerhead diameter to obtain uniform velocity field above the substrate. The thickness non-uniformity of GaN films grown at 600 °C was improved from 5.14% to 1.86% after the optimization of showerhead. On that basis, the influence of triethylgallium (TEG) and trimethylgallium (TMG) on low-temperature GaN growth were investigated and TEG was proved to be the more appropriate Ga source in this case. Finally, GaN film with high c -axis and in-plane orientations was obtained on sputtered AlN/sapphire template and the full width half maximums of (002) and (102) x-ray rocking curves are 0.45° and 0.57° respectively. Our results provide a practicable method for the optimization of low-temperature MOCVD, which has potential to obtain large-scale crystalline films at low temperature.